2017
DOI: 10.1016/j.kint.2017.03.030
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, proteomics study identified potential biomarkers of encapsulating peritoneal sclerosis in peritoneal effluent

Abstract: Encapsulating peritoneal sclerosis (EPS) is a potentially devastating complication of peritoneal dialysis (PD). Diagnosis is often delayed due to the lack of effective and accurate diagnostic tools. We therefore examined peritoneal effluent for potential biomarkers that could predict or confirm the diagnosis of EPS and would be valuable in stratifying at-risk patients and driving appropriate interventions. Using prospectively collected samples from the Global Fluid Study and a cohort of Greek PD patients, we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 71 publications
2
20
0
2
Order By: Relevance
“…The study by Oliveira et al found strong protein abundance of Factor D in six adult PD patients ( 81 ), whereas a similar approach in 76 PD patients by Wen et al found significant protein expression of C4 and C3 only ( 82 ). Altogether, proteomic analyses of the dialysate of healthy PD patients has revealed the presence of C4, C3, Factor B, Factor D, Factor H, Factor I, and C9 ( 81 85 ). Proteomic profiling in the peritoneal fluid of children identified a total number of 189 proteins, of which 18 complement components ( 84 ).…”
Section: Peritoneal Dialysismentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Oliveira et al found strong protein abundance of Factor D in six adult PD patients ( 81 ), whereas a similar approach in 76 PD patients by Wen et al found significant protein expression of C4 and C3 only ( 82 ). Altogether, proteomic analyses of the dialysate of healthy PD patients has revealed the presence of C4, C3, Factor B, Factor D, Factor H, Factor I, and C9 ( 81 85 ). Proteomic profiling in the peritoneal fluid of children identified a total number of 189 proteins, of which 18 complement components ( 84 ).…”
Section: Peritoneal Dialysismentioning
confidence: 99%
“…The bioincompatibility of these solutions presumably promotes the expression TGF-b, thereby stimulating the transition of mesothelial cells to myofibroblasts. Recently, a prospective proteomics study identified complement components as a possible biomarker of encapsulating peritoneal sclerosis ( 85 ). Factors B and factor I were elevated in the PD fluid of patients up to 5 years prior to developing encapsulating peritoneal sclerosis.…”
Section: Peritoneal Dialysismentioning
confidence: 99%
“…Strikingly, the most abundant corona protein (full‐length cDNA clone, CS0DD006YL02), which contributed to 8% of the total protein content, was not detected in any of the plasma control samples (Figure C; Table S4, Supporting Information). Although, full‐length cDNA clone CS0DD006YL02 has been previously identified by mass spectrometry analysis of arachnoid cyst fluid, peritoneal effluent and saliva, current proteomic approaches fail to detect this low‐abundance protein in complex mixtures like plasma.…”
mentioning
confidence: 99%
“…Nevertheless, previous proteomic efforts to develop novel PDE biomarkers have been hindered by the PDE's plasma-like dynamic range of protein abundances, by the limited performance of separation and detection techniques applied to date, and by the design of the clinical trials from which the PDE samples were obtained. Thirteen published proteomic analyses of soluble PDE proteins have to date identified 171 unique proteins ( 7 19 ).…”
mentioning
confidence: 99%